A unique case of foreign body aspiration and recurrent pneumothorax - Mario Lima; Sara Ugolini; Niel Di Salvo; Michele Libri; Tommaso Gargano; Giovanni Ruggeri (PAGEPress Publications, 2017)
Paediatric foreign body aspiration can be related to a high morbidity/mortality rate, especially in young children, and pneumothorax can be a severe associated issue. We describe a case of a 13-year-old girl with recurrent pneumothorax in bilateral bullous lung, twice previously treated at our institution by robotassisted bullectomy, and once again showing same signs and symptoms. At conventional thoracoscopy an inorganic foreign body was found to be located pointing upwards the apex. We believe this may have acted as a contributory cause in the persistence of the clinical picture, despite the surgical removal of the underlying pathology.